Teachers’ Perspectives on Gamification in ELT: Enhancing Student Engangement Through ICT - Nur Layli Faiqiah; Christianti Tri Hapsari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Gamification has emerged as a promising instructional strategy to address low student engagement in English language classrooms. While previous studies show its effectiveness in enhancing motivation, limited research focuses on how pre-service teachers apply gamification supported by Information and Communication Technology (ICT) during teaching practicum. This study aims to explore how gamification is used to increase student engagement and the challenges faced by pre-service English teachers. Using a qualitative descriptive design, data were collected from 20 respondents through open-ended questionnaires based on Engagement Theory. The findings show that gamification fosters collaboration, creativity, and real-world application of English through interactive platforms like Kahoot! Quizizz, and Wordwall. However, challenges such as limited ICT infrastructure, time constraints, and lack of training were also identified. The study concludes that with thoughtful design and support, gamification can be a powerful pedagogical approach to promote meaningful engagement in English language learning.